Penggunaan Elektronik Modul Pemasangan Alat Kontrasepsi dalam Rahim sebagai Metode Blended Learning untuk Meningkatkan Keterampilan Mahasiswa Diploma Tiga Kebidanan: Penelitian Kuasi Eksperimen - Musdalifah, Musdalifah; Usman, Andi Nilawati; Arsyad, M. Aryadi; Arifuddin, Sharvianty; Nontji, Werna; Baso, Yusring Sanusi (PT Karya Inovasi Berkelanjutan, 2026)
Introduction and Methods This study aimed to determine the efficacy of e-modules in enhancing the clinical skills of Diploma III (DIII) midwifery students. A quasi-experimental method was employed using a pre-test and post-test control group design. The population comprised all second-year DIII midwifery students at the Pelamonia Institute of Health Sciences. A total sampling technique was applied, resulting in a sample of 72 students, divided equally into intervention and control groups (n=36 each). Skill levels were assessed prior to the intervention using a standardized checklist. Data were analyzed using the Wilcoxon signed-rank test and the Mann-Whitney U test. Results The Wilcoxon signed-rank test results indicated that both the control group (printed module) and the intervention group (electronic module) experienced significant improvements in skill levels (p=0.000). However, the Mann-Whitney U test revealed a significant difference in score improvements between the two groups (p=0.000 < α=0.05). The intervention group achieved a significantly higher increase in skill scores compared to the control group. Conclusion and Suggestions The use of a blended learning-based electronic module for Intrauterine Device (IUD) insertion is significantly more effective in enhancing the skills of DIII Midwifery students than traditional printed modules. While both instructional methods facilitate skill development, the intervention group demonstrated a markedly superior improvement (p=0.000). The developed e-module has been validated by media and content experts, is deemed highly feasible for implementation, and offers distinct advantages in terms of flexibility, accessibility, and support for self-directed learning. Contribution to Sustainable Development Goals (SDGs) This study contributes to the achievement of SDG Target 3.c regarding the enhancement of health workforce development and training, as well as Target 3.7 concerning universal access to sexual and reproductive health-care services and family planning. Through the development of blended learning-based e-modules, this study offers an effective training method to improve the clinical skills of prospective midwives in Intrauterine Device (IUD) insertion. Enhancing these core competencies ensures that the public receives high-quality, safe, and professional contraceptive services, ultimately supporting global reproductive health agendas.